FRI0189 POOLED ANALYSIS OF THE REAL-WORLD EFFECTIVENESS OF BELIMUMAB IN TREATMENT OF SYSTEMIC LUPUS ERYTHEMATOSUS USING MULTI-COUNTRY DATA FROM THE OBSERVE STUDIES. (June 2019) - Collins, Christopher; Cortés-Hernández, Josefina; García, Mercedes; Kempis, Johannes von; Schwarting, Andreas; Touma, Zahi; Ferrante, Shannon; Kurtinecz, Milena; Gairy, Kerry
Abstract : Background: Real-world evidence of belimumab effectiveness in patients with systemic lupus erythematosus (SLE) has been reported separately for several countries through the OBSErve (evaluation Of use of Belimumab in clinical practice SEttings) programme. Objectives: To evaluate the effectiveness of belimumab in patients with SLE using pooled data from the individual OBSErve studies. Methods: This was a post hoc meta-analysis (GSK study 206351) of patient level data pooled from six retrospective observational cohort studies (Argentina, Canada, Germany, Spain, Switzerland, United States of America). Physicians provided data for adults (≥18 years; clinical diagnosis of SLE) who had initiated intravenous belimumab as part of their usual SLE care ≥6 months prior to enrolment and for whom reasons for belimumab initiation could be identified. Primary objective: physician-assessed overall clinical response to belimumab at Month 6, which reflected physicians' impression of change in overall clinical manifestations, categorised as worse, no improvement, and improvement of <20%, 20–49%, 50–79%, and ≥80%. Secondary objectives included a description of patient characteristics at belimumab initiation (index); treatment patterns during the 6 months after index; and patient and treatment characteristics associated with an overall clinical response. Safety was not assessed. Results: Data were pooled from all 830 patients (89.3% female; mean [standard deviation] age 41.9 [12.6] years) included in each of the OBSErve studies. At index, most patients had moderate SLE (71.4%; physician-assessed) and serological indicators of high disease activity (82.8%; high anti-dsDNA and/or low complement). Of 345 patients for whom Safety of Estrogens in Lupus Erythematosus-National Assessment Trial-SLE Disease Activity Index baseline data were available, 60.0% had a score ≥10. At index, 72.0% of patients had musculoskeletal, 59.0% had mucocutaneous manifestations, and 16.5% had renal involvement. At Month 6, 82.8% of patients had ≥20% improvement and 48.1% had ≥50% improvement in their overall condition; only 4.7% had none or a worse response to belimumab therapy (Figure ). At index, 81.4% of patients received steroids at a mean dose of 17.6 mg/day. At Month 6, the mean change in steroid dose was –9.7 mg/day. Of those receiving a dose >7.5 mg/day (78.4% of all patients receiving steroids at index), 54.5% had a dose reduction to ≤7.5 mg/day at Month 6. Ineffective previous treatment was the main reason for belimumab initiation (74.3%). Prior to Month 6, 4.4% of patients (n=12/270) in Argentina, Spain, Germany and Switzerland discontinued belimumab, most frequently due to lack of efficacy and patient request (both 33.3%); OBSErve US and Canada excluded patients with <6 months' belimumab treatment. Conclusion: This study provides important insights into global real-world outcomes in a large number of patients with SLE treated with belimumab. After 6 months of treatment, most patients demonstrated clinical improvements in SLE; results were consistent across the pooled population and for patients with high disease activity. Belimumab was steroid sparing; most patients receiving steroids at belimumab initiation decreased their steroid dose after 6 months of belimumab treatment. Acknowledgement: Study funded by GSK. Gosia Carless, PhD, Fishawack Indicia Ltd, UK, provided editorial assistance funded by GSK. Disclosure of Interests: Christopher Collins Grant/research support from: Exagen, Consultant for: Exagen, AbbVie, Speakers bureau: Exagen, AbbVie, Novartis, Josefina Cortés-Hernández Grant/research support from: GSK, Speakers bureau: GSK, Mercedes García Grant/research support from: GSK, Speakers bureau: GSK, Johannes von Kempis: None declared, Andreas Schwarting Grant/research support from: GSK, Pfizer, AbbVie, Novartis, Roche, Speakers bureau: GSK, Novartis, Zahi Touma Grant/research support from: GSK Canada, Consultant for: UBC, Pfizer, Janssen, Inc, Shannon Ferrante Shareholder of: GSK, Employee of: GSK, Milena Kurtinecz Shareholder of: GSK, Employee of: GSK, Kerry Gairy Shareholder of: GSK, Employee of: GSK